Baṣāʼir-i Ḥakīmulummat : ḥaqīqat-i taṣṣavuf o sulūk o izālah-yi auhām o shukūk - Thānvī, Ashraf ʻAlī (Idārah Ishāʻat-i Islām, 1978)
An exposition of various aspects of Sufism by d Deobandi religious scholar.